Surgical Masks Affect the Peripheral Oxygen Saturation and Respiratory Rate of Anesthesiologists - Yang, Shaozhong; Fang, Chuanyu; Liu, Xin; Liu, Yu; Huang, Shanshan; Wang, Rui; Qi, Feng (Frontiers in Medicine, 2022)
Background Surgical masks protect medical staff and reduce surgical site infections. Extended Surgical mask use may reduce oxygen concentrations in circulation, causing hypoxia, headache and fatigue. However, no research has examined the effects of wearing surgical masks on oxygenation and physical discomfort of anesthesiologists. Methods An electronic questionnaire was established and administered through WeChat, and a cross-sectional survey was conducted to determine surgical mask use duration and related discomfort of operating room medical staff. Then, operating room anesthesiologists were enrolled in a single-arm study. SpO2, heart rate and respiratory rate were determined at different times before and after surgical mask use. Shortness of breath, dizziness and headache were subjectively assessed with visual analog scales. Results In total, 485 operating room medical staff completed the electronic questionnaire; 70.5% did not change surgical masks until after work, and 63.9% wore surgical masks continuously for more than 4 hours. The proportion of anesthesiologists was the highest. After wearing masks for 4 hours, the shortness of breath, fatigue, and dizziness /headache rates were 42.1%, 34.6% and 30.9%, respectively. Compared with other medical staff, the proportion of subjective discomfort of anesthesiologists increased significantly with prolonged surgical mask use from 1 hour to 4 hours. Thirty-five anesthesiologists completed the study. There was no difference in anesthesiologist SpO2, heart rate or respiratory rate within 2 hours of wearing surgical masks. After more than 2 hours, SpO2 was statistically rather than clinical significantly decreased (98.0 [1.0] vs. 97.0 [1.0], P < 0.05), respiratory rate was increased (16.0 [3.0] vs. 17.0 [2.0], P < 0.01), and heart rate was unchanged. As mask use duration increased, the visual analog scales of shortness of breath, dizziness and headache gradually increased. Conclusion In healthy anesthesiologists, wearing surgical masks for more than 2 hours can significantly decrease SpO2 and increase respiratory rates without affecting heart rates. Keywords: anesthesiologists, heart rate, peripheral oxygen saturation, respiratory rate, surgical mask